Super growth of vertically-aligned carbon nanofibers and their field emission properties - Kan, JungHo; Shin, Dong Hoon; Yun, Ki Nam; Masud, Felisita Annisanti; Lee, Cheol Jin; Kim, Myung Jong (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
We demonstrate a very efficient synthesis of vertically-aligned ultra-long carbon nanofibers (CNFs) with sharp tip ends using thermal chemical vapor deposition. Millimeter-scale CNFs with a diameter of less than 50 nm are readily grown on palladium thin film deposited Al2O3 substrate, which activate the conical stacking of graphitic platelets. The field emission performance of the as-grown CNFs is better than that of previous CNFs due to their extremely high aspect ratio and sharp tip angle. The CNF array gives the turn-on electric field of 0.9 V/mu m, the maximum emission current density of 6.3 mA/cm(2) at 2V/mu m, and the field enhancement factor of 2585. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: NANOTUBES; NANOPARTICLES; PALLADIUM; DECOMPOSITION; NUCLEATION; DIFFUSION; MECHANISM; ETHYLENE; ARRAYS